Poor quality of sewage water in Ukraine: a priority in post-war rebuilding - Ilias Shcherbakov; Kateryna Bryleva; Rebecca Strawbridge; Milena Nikolajeva; Nataliya Matkovska; Vladimir Kravec; Dennis Ougrin; Allan H. Young (Scientific Reports)
Abstract The presence of toxic chemicals in sewage has implications for human health but evidence is lacking. The current study aimed to delineate the state of pollution of sewage water in Ukraine before the full-scale Russian invasion in 2022. Ten sampling locations around the country were selected, varying by population and industry level. We used inductively coupled plasma optical emission spectroscopy (ICP-OES) to analyse Aluminium, Cadmium, Copper, Iron, Manganese, Nickel, Lead and Zinc concentrations in the sewage water. Sewage water samples from Kharkiv and Lviv showed 100 to 1000 times higher levels of heavy metals than considered safe. It is shown that samples from high urban and industrial regions have significantly higher levels of pollutants than in other cities. The concentration of metals in water samples collected in the evening was higher than the morning of the same day. Furthermore, there was a marked increase in levels of metals on weekdays compared to weekends. The anomalous increases coincided with peak times of large factory operations/works. Our results have significant implications for authorities responsible for environmental health at regional, national, and international levels, given the implications for water consumers in Ukraine. During the post-war rebuilding, sewage water treatment improvement should be prioritised.